2011
DOI: 10.19030/jabr.v20i4.2225
|View full text |Cite
|
Sign up to set email alerts
|

Management Compensation And Project Life

Abstract: <p class="MsoNormal" style="text-align: justify; margin: 0in 0.5in 0pt; mso-hyphenate: none;"><span style="font-family: &quot;Times New Roman&quot;,&quot;serif&quot;; letter-spacing: -0.15pt; color: black; font-size: 10pt;">The goal of this paper is to empirically examine the relation between management compensation and project life.<span style="mso-spacerun: yes;">&nbsp; </span>Prior theoretical research suggests that short-term compensation, in the form of bonus pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Porter (1992) argues that the uncertain nature of R&D investment may encourage managers to under invest in R&D to the detriment of shareholders. It has been shown that managers adjust R&D spending in response to meet current-period earnings performance (Baber et al, 1991;Perry and Grinaker, 1994;Bange and De Bondt, 1998;Bushee, 1998;Cheng, 2004), to exceed analysts' earnings forecasts (Bhojraj et al, 2009), and to meet earnings-based compensation (Bange and De Bondt, 1998;Harter and Harikumar, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Porter (1992) argues that the uncertain nature of R&D investment may encourage managers to under invest in R&D to the detriment of shareholders. It has been shown that managers adjust R&D spending in response to meet current-period earnings performance (Baber et al, 1991;Perry and Grinaker, 1994;Bange and De Bondt, 1998;Bushee, 1998;Cheng, 2004), to exceed analysts' earnings forecasts (Bhojraj et al, 2009), and to meet earnings-based compensation (Bange and De Bondt, 1998;Harter and Harikumar, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the nature of R&D investment and its returns may lead to the agency problem of a less than optimal investment in R&D (Porter, 1992). There is evidence that managers intentionally underinvest in R&D to meet an earnings target (Graham, Harvey, & Rajgopal, 2005), to facilitate a pending stock issuance (Bhojraj & Libby, 2005), to meet earnings-based compensation goals (Harter & Harikumar, 2004), and to beat analysts' earnings forecasts (Bhojraj, Hribar, Picconi, & McInnis, 2009). …”
Section: Introductionmentioning
confidence: 99%